Noticiario arqueológico - Ruiz Valderas, Elena; Salmerón Juan, Joaquín; Jiménez Lorente, Sacramento; Iniesta Sanmartín, Ángel; Manzano Mar´tinez, José; Lechuga Galindo, Manuel; Mart´ínez Rodríquez, Andrés (Antigüedad y Cristianismo, 1988)
*